(untitled) (Research, Society and Development, 2022)
The objective was to evaluate the physical and microbiological quality of different types of eggs sold in the city of São Luís, MA. A total of 240 eggs were analyzed, 60 white eggs, 60 red eggs, 60 enriched eggs and 60 free-range eggs. The temperature and relative humidity of the commercial environment were evaluated. Individual eggs were weighed and quality aspects related to shell, albumen and yolk were evaluated. Microbiological analyzes were performed for the most likely number of thermotolerants, counts of mesophilic aerobic microorganisms and search for Salmonella spp. in the shell and internal content of the eggs. In the egg commercialization environment, the temperature ranged from 27.50ºC to 32.20ºC and relative humidity from 62.75% to 76%. White eggs had worse shell quality, due to the presence of cracks (1.25%), dirt (8.75%), cage marks (11.66%) and with thin shells (15.41%). The average egg weight ranged from 57.87g to 60.19g, according to product labeling. The Haugh unit ranged from 51.44uH for white eggs to 62.32uH for free-range eggs. All types of eggs had mesophilic aerobic microorganism counts of 1.44x104 CFU/g. The free-range eggs showed contamination by Salmonella spp. in 2.08% in the shell of the analyzed eggs. The white eggs were the only ones that showed the presence of Salmonella spp. in the internal content. The results obtained suggest that the different types of eggs presented good physical and microbiological quality. However, there is the presence of Salmonella spp. indicating risk to the health of consumers.